NATIONAL STANDARDS WITH INTERNATIONAL STANDARDS REQUIREMENTS FOR HARMONIZATION (American Journal of Pedagogical and Educational Research, 2026)
This article covers the requirements and rules for measuring harmonized standards, describing the test method, or applying it in a specific sector when harmonizing our national standards with international standards.